A quick method of obtaining double mutants and heterocaryon compatible isolates from mutants derived from foreign stocks - M, Ahmad (Fungal Genetics Reports, 1962)
A quick method of obtaining double mutants and heterocaryon compatible isolates from mutants derived from foreign stocks